Supply Chain Strategy in Public Budgeting Process: System-Efficacy as Intervening Variable - Yuhertiana, Indrawati; Suhartini, Dwi; Mohamed, Nafsiah; Tannar, Oryza; Julianto Harsono, Eddy (ExcelingTech, 2020)
Abstract— Rapid challenges and changes that are an integral part of the business environment require companies to plan their business carefully, as well as to assess the probability of future events occurring and resulting from them. Supply chain strategy research in budgeting in the public sector is interesting to study. The main target of the current paper is to analyze the impact of the participatory budgeting on the dysfunctional supply chain strategy mediated by self-efficacy in the public sector. The population was executive officers in the regional government of the province of East Java, Indonesia. Quota sampling is used to determine unit samples. Data obtained from 130 respondents. Three hypotheses were tested using Partial Least Square Analysis. Participative budgeting has been proven to increase self-efficacy. Self-efficacy has also been proven to be an intervening variable, by being able to reduce dysfunctional supply chain strategy with involvement in budgeting. On the other hand, participative budgeting influences dysfunctional supply chain strategy in a positive direction. The practical implications of this study are used as a basis for decision making for local governments in designing management control systems, especially in the budgeting process and paying attention to the character of personal self-efficacy.